Lipid-based microtubes for topical delivery of Amphotericin B - Salerno, Claudia (2013)
The self-assembly process is a valuable tool for constructing nano and microstructures. Microtubes (MTs)self-assembled from amphiphiles are novel promising nanomaterials as they have easy self-assembly in aqueous solutions, reproducibility and biocompatibility. The incorporation of amphotericin B (AmB)into lipid microtubes formed from 12-hydroxystearic acid (12HSA) when mixed with ethanolamine in aqueous media was investigated. MTs of several concentrations of lipid material and AmB were prepared. The structure was characterized by phase-contrast microscopy, TEM and SEM. The type of interaction was analyzed by FTIR and DSC. Stability studies were carried out at room temperature and at 4 ◦C. Loading efficiency of the system was found to be much higher than the drug solubility in water. MTs with 1% of 12HSA and 1 mg/ml of AmB showed to be the most stable formulation. In vitro skin penetration assay showed a flux of 18.20 ± 3.35 g/cm2. Amb-loaded MTs in vitro antifungal activity was evaluated and formulation showed similar results to that of AmB deoxycholate showing that AmB retained its antifungal activity in the MTs formulation.